Excavating the Future Archaeology and Geopolitics in Contemporary North American Science Fiction Film and Television (Volume 57) - Malley, Shawn (Liverpool University Press, 2018)
Well-known in science fiction for tomb-raiding and mummy-wrangling, the archaeologist has been a rich source for imagining 'strange new worlds' from 'strange old worlds.' But more than a well-spring for SF scenarios, the genre's archaeological imaginary invites us to consider the ideological implications of digging up the past buried in the future. A cultural study of an array of very popular, though often critically-neglected, North American SF film and television texts-running the gamut of telefilms, pseudo-documentaries, teen serial drama and Hollywood blockbusters-Excavating the Future explores the popular archaeological imagination and the political uses to which it is being employed by the U.S. state and its adversaries. By treating SF texts as documents of archaeological experience circulating within and between scientific and popular culture communities and media, Excavating the Future develops critical strategies for analyzing SF film and television's critical and adaptive responses to post 9/11 geopolitical concerns about the war on terror, homeland security, the invasion and reconstruction of Iraq, and the ongoing fight against ISIS.